2011
DOI: 10.1007/s00464-011-2076-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic right colectomy in an unselected patient population

Abstract: Single-incision laparoscopic colectomy is feasible, safe, efficient, and oncologically sound for most patients who are seen in a typical colorectal practice. These data are useful as single-incision laparoscopic colectomy becomes more broadly implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Rather, both remained consistent with other reported series of both single-port and multiport laparoscopic colectomies [10,[12][13][14]. This suggests that the key to determining patient recovery may not lie within the approach between single or multi-port laparoscopy, and instead hinders on the nature of the operation itself and/or inherent patient factors.…”
Section: Discussionsupporting
confidence: 86%
“…Rather, both remained consistent with other reported series of both single-port and multiport laparoscopic colectomies [10,[12][13][14]. This suggests that the key to determining patient recovery may not lie within the approach between single or multi-port laparoscopy, and instead hinders on the nature of the operation itself and/or inherent patient factors.…”
Section: Discussionsupporting
confidence: 86%
“…We can conclude from the PubMed literature search that single‐incision laparoscopic hemicolectomy can be performed safely in selected patients. Complications reported in the literature are: conversion [5–10], postoperative wound infection [9,11], intra‐abdominal abscess [9], anastomosic bleeding [12–14], pulmonary complications [15], wound haematoma requiring evacuation [13], urinary tract infection [16], ileus [13,16], chest infection [17], seroma [9,14] and subobstruction because of adhesions [9,14]. In our study, one chest infection occurred.…”
Section: Discussionmentioning
confidence: 76%
“…All margins were tumour-free for at least 3 cm. The median (range) number of harvested lymph nodes in the specimen was 13.5 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…Conventional ML-RH has aroused interest among many surgeons since its inception and has gradually become one of the most widely performed surgical procedures in the treatment of colon cancer [3,24]. ML-RH has been proven as a safe technical alternative to O-RH for patients with colon cancer, in terms of minimal invasion, faster postoperative recovery, and lower rates of wound infection.…”
Section: Discussionmentioning
confidence: 99%
“…Ceppa et al [21] reported that SIL-RH was associated with a slightly higher cost than ML-RH, with the difference in cost being eliminated by the multiple use of the reusable optical system. Boone et al [24] concluded that SIL-RH was associated with a 27 % lower mean operative cost and a 10 % lower mean total cost compared with ML-RH. On the other hand, Mufty et al [25] concluded that SIL-RH was associated with a higher cost than ML-RH, with the single-incision extra port being responsible for the extra cost.…”
Section: Discussionmentioning
confidence: 99%